DEVELOPMENT OF SERVICES IN IMPROVING THE QUALITY OF LIFE OF THE POPULATION (American Journal of Interdisciplinary Research and Development, 2023)
In this article, views aimed at improving the quality and efficiency of services in the service sector are considered, and the problems of the development of services in rural areas today are detailed. In addition, there are suggestions and recommendations for raising the standard of living of the population.